A female-emitted pheromone component is associated with reduced male courtship in the parasitoid wasp Spalangia endius - Mowles, Sophie L.; King, Bethia H.; Linforth, Robert S.T.; Hardy, Ian C.W. (Public Library of Science, 2013)
During courtship interactions, the courted individual may not always be prepared to mate. For example, mating or courtship may be detrimental to its fitness and resistance is expected under these circumstances. As such, various resistance strategies have evolved, from physically fending off courting individuals to producing behavioural signals of unreceptivity. In the parasitoid wasp Spalangia endius, females rarely re-mate and mated females are avoided by males in favour of virgin females. Further, mated females appear to advertise their mating status by the release of a pheromone component (methyl 6-methylsalicylate), but direct evidence of the nature of this release is lacking. Here we used real-time chemical analysis to track the emission of the pheromone component during courtship interactions between virgin males and either virgin or mated females. We found that females actively release methyl 6-methylsalicylate when courted and that significantly greater concentrations are released by previously mated females. Further, high concentrations of this component are associated with both the prevention and termination of courtship.